Pengelolaan Konten Media Sosial pada Akun Instagram @indozone.id Dalam Upaya Meningkatkan Followers Instagram - Alfarizqi, Salman; Mayasari, Mayasari; Nurkinan, Nurkinan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Social media has become a phenomenon that dominates technological development in recent decades. Since its inception, social media has experienced rapid growth around the world, including in Indonesia. The presence of social media has changed the way people interact, share information, and establish social relationships. This is utilized by digital companies such as Indozone, which presents educational news and information content to reach more targets through the Instagram social media account @indozone.id. This study aims to determine how efforts to manage social media content on the @indozone.id Instagram account in an effort to increase followers using The Circular Model of SOME theory from Regina Luttrell. This research uses descriptive qualitative research methods with research data obtained from in-depth interviews, non-participant observation, documentation and literature study. The results of this study indicate that the efforts to manage social media content on the @indozone.id Instagram account using The Circular Model of SOME theory have an impact on increasing the number of followers of the @indozone.id Instagram account. Keywords: Content; Social Media; Followers